The Cinema of Exposure: Spiritualist Exposés, Technology, and the Dispositif of Early Cinema - Natale, Simone (Recherches sémiotiques / Semiotic Inquiry)

(untitled) (Association canadienne de sémiotique / Canadian Semiotic Association, 2011)
This article addresses the relationship between early cinema and the tradition of spiritualist exposés. The latter were spectacular shows performed by stage magicians in the nineteenth and early twentieth century, which aimed to debunk the tricks employed by spiritualist mediums in their séances. Drawing on the theoretical framework of the dispositif, this article shows how early cinema renewed and reinterpreted the tradition of the exposés. Focusing in particular on Hugo Münsterberg’s work, moreover, it addresses the connections between early film theory and psychological studies that debunked the illusions performed in spiritualist séances and stage magic. In the conclusion, the article proposes to employ the concept of “cinema of exposure” in order to address how early cinema invited spectators to acknowledge their own perceptual delusion.